Mercury Content in Well Water and Public Health Complaints: Study Around Small-Scale Gold Mining in Jember Regency - Violita, Dinda Windi; Ma'rufi, Isa (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Small-Scale Gold Mining is a community activity that is generally without permits. This activity contributes to negative impacts on the environment and society due to the use of mercury in gold processing. Waste containing mercury is not processed and is immediately disposed of in the environment. This research aims to determine the mercury content in community well water around Small-Scale Gold Mining and public health complaints. This research is a descriptive study with the research variables being the mercury content of healthy water, the distance of the well to the source of pollution, the condition of the sound construction, the use of the well, and public health complaints. This research involved 13 wells and 46 communities as respondents. Based on the measurements, interviews, and observations that have been carried out, it was obtained that the mercury content in 13 community wells water showed where these results are below environmental quality standards according to Minister of Health Regulation No. 32 of 2017. Three community wells do not meet the requirements for good sanitation and healthy spacing, and several community wells need to meet the requirements, such as walls and floors that are not watertight. Health complaints people feel include itching, redness of the skin, and itching and burning in the eyes. A few respondents around Small-Scale Gold Mining only felt these health complaints. Research shows that Small Scale Gold Mining activities have not polluted community water sources, namely well water, and have not caused significant public health complaints.